Agus Muhammmad Iqdam Khalid's Da'wah (Gus Iqdam): A Rhetoric Analysis - Candra, M. Khoirun; Anam, Moh Khoirul (Proceedings of International Conference on Da'wa and Communication, 2023)
The rhetoric of preaching is the art of public speaking aimed at inviting individuals to the path of Allah SWT in accordance with Islamic principles. This research focuses on the rhetorical analysis of Agus Muhammad Iqdam Kholid's preaching in the context of media. The research objective is to comprehend the rhetorical style employed by Agus Muhammad Iqdam Kholid when delivering lectures through media. The research methodology used is a qualitative approach with Miles and Huberman's data analysis method, involving steps of data reduction, data presentation, and conclusion drawing. Data was obtained through watching and listening to videos and participating in the routine lectures of Gus Muhammad Iqdam Kholid. This study applies a descriptive qualitative method using Aristotle's persuasive rhetoric theory, known as Aristotle's rhetorical triangle, encompassing ethos, pathos, and logos as ways to influence the audience. The research findings indicate that Agus Muhammad Iqdam Kholid consistently applies Aristotle's rhetorical triangle. With high credibility, Agus Muhammad Iqdam Kholid successfully evokes emotions in the audience during his lectures. As a young Da'i, he has a substantial following and inspires the youth. Importantly, he does not discriminate based on caste, status, rank, or position among the congregation and guests attending his lectures. Gus Iqdam often uses the Javanese language, referring to his audience as "Garangan" to denote individuals from the street or marginalized youth. One expression ingrained in the memory of the audience is "dekengane wong pusat," conveying the meaning of always being under the protection of Allah SWT. Despite using the Javanese language, Gus Iqdam's influence remains potent in his routine lectures and the comment section of live preaching videos on Sabilu Taubah Official and Gus Iqdam Official media platforms.